Bullying and Self-Esteem in Elementary School Students: Findings from A Study in Montería, Colombia - Velásquez, Oscar Andrés Vargas; Murillo, Hernán Javier Guzmán; Ortega, José Marcelo Torres (Journal of Posthumanism, 2025)
The quantitative study, with a descriptive-correlational scope and cross-sectional section, explored the relationship between bullying and self-esteem in 34 third-grade students from an educational institution in Montería (Colombia). The AEPAE Incidence Test was applied to classify bullying into three risk levels and the Rosenberg Self-Esteem Scale to estimate personal self-assessment. The results showed that 29.4% of the group is at high risk of bullying, 55.9% at medium risk and 14.7% at low risk, so that more than 85% have some degree of vulnerability to the phenomenon. Regarding self-esteem, 88.2% reported medium level, 8.8% high level and 2.9% low level, indicating an overall stable self-perception, although with pockets of insecurity that require follow-up. Spearman’s coefficient showed a negative correlation (rs = -0.285) between both variables, without statistical significance (p = 0.102), so the increase in bullying behaviors was not conclusively associated with the decrease in self-esteem in this sample. Even so, the magnitude of cases at medium and high risk underscores the urgency of designing preventive interventions that combine teacher-family awareness, active listening spaces, and socio-emotional strengthening programs. It is recommended to expand the sample and delve into mediating variables —gender, family climate, and school support— to clarify patterns and strengthen future policies of school coexistence.